The Use of Clay-Polymer Nanocomposites in Wastewater Pretreatment - Giora Rytwo (The Scientific World Journal)
Some agricultural effluents are unsuitable for discharge into standard sewage-treatment plants: their pretreatment is necessary to avoid clogging of the filtering devices by colloidal matter. The colloidal stability of the effluents is mainly due to mutual repulsive forces that keep charged particles in suspension. Pretreatment processes are based on two separate stages: (a) neutralization of the charges (“coagulation”) and (b) bridging between several small particles to form larger aggregates that sink, leaving clarified effluent (“flocculation”). The consequent destabilization of the colloidal suspension lowers total suspended solids (TSSs), turbidity, and other environmental quality parameters, making the treatments that follow more efficient. Clay-based materials have been widely used for effluent pretreatment and pollutant removal. This study presents the use of nanocomposites, comprised of an anchoring particle and a polymer, as “coagoflocculants” for the efficient and rapid reduction of TSS and turbidity in wastewater with a high organic load. The use of such particles combines the advantages of coagulant and flocculant by neutralizing the charge of the suspended particles while bridging between them and anchoring them to a denser particle (the clay mineral), enhancing their precipitation. Very rapid and efficient pretreatment is achieved in one single treatment step.